Adult-onset linear discoid lupus erythematosus on the forehead mimicking en coup de sabre: A case report - Sasipaka Sindhusen (2020)
© 2019 The Author(s). Background: Linear cutaneous lupus erythematosus (LE) is an unusual form of LE-specific cutaneous condition, occurring in children and young adults. Due to its rarity, the diagnosis of linear cutaneous LE can be difficult and facial lesions can resemble linear morphea or en coup de sabre. Differential diagnosis of similar conditions along the lines of Blaschko must be differentiated from linear LE. Case presentation: We report a case of linear discoid LE on the forehead of an adult female Thai patient mimicking en coup de sabre. The dermatoscopy, histopathology and direct immunofluorescence findings were consistent with chronic cutaneous LE. Conclusions: As this patient demonstrated classic dermatoscopic features of LE, we emphasized that the diagnosis of linear cutaneous LE can be made by dermatoscopy. This is particularly beneficial for young self-conscious patients with facial lesions that are reluctant to perform skin biopsy.